Ativação de Receptores Glutamatérgicos Metabotrópicos do Grupo I despolariza e aumenta a excitabilidade dos neurônios do Corpo Trapezoide de camundongos neonatos - Éverton dos Santos e Alhadas (2014)
Group I metabotropic glutamate receptors (mGluR-I) are coupled to protein Gq which are involved in the formation of PLC / IP3 and release of Ca2 + from intracellular stores. Previous studies have shown that activation of mGluR-I receptors in the Medial Nucleus of the Trapezoid Body generates an inward current at membrane potentials near the resting potential, suggesting an excitatory role for these receptors. In order to test this hypothesis, we performed experiments in slices of brainstem regions containing the trapezoid body obtained from C57BL mice, 6-9 days old, of both sexes. Standard intracellular recordings were performed using glass pipettes filled with 2 M KCl, producing resistances of 110-160 MOhm, in order to measure the membrane potential and action potentials. Recordings were performed in control situations, during application of the selective agonist for mGluR-I, DHPG (100 mM), and again after washing DHPG from the bath. Application of DHPG generated a depolarization of 5.5 ± 0.55 mV (n = 13). This DHPG-induced depolarization was partially inhibited by MPEP (10 mM), a selective mGluR5 antagonist. This inhibition was significantly greater when MPEP was applied together with LY367385 (240 mM) a selective antagonist for mGluR1. During application of DHPG, the threshold of excitability was reduced by 186.4 ± 54 pA (n = 11), and the neurons fired action potentials at higher frequency. Both effects were reverted after washout of DHPG with drug-free solution. The effects of DHPG on action potentials could have been simply a consequence of the induced depolarization, or could be a reflection of a change in the intrinsic excitability of neurons. To distinguish these possibilities, we used protocols that combine injection of depolarizing current with the application of DHPG and compared the effects of both in the same cell. We observed that a depolarization of 5 mV did not completely mimick the effects of DHPG (N = 3). We conclude that, in addition to generating a depolarization, activation of mGluR-I receptors alter the excitability of trapezoid body neurons.